Graphene Based Triboelectric Nanogenerators Using Water Based Solution Process - Domingos, Ismael; Neves, Ana I. S.; Craciun, Monica F.; Alves, Helena (Frontiers in Physics, 2021)
A rapid development in personal electronics has raised challenging requirements for portable and sustainable power sources. For example, in wearable technologies, the concept of wearable body area network (WBAN) brings body motion and vital signs monitoring together in synergy. For this, a key aspect is sustainable portable energy, available anywhere, at any time, as generated by triboelectric nanogenerators (TENG). This technology usually demands high-cost processes and materials and still suffer from low power output, as well as unstable output values due to charge generating stimulus with variable intensities. In this work, we present TENGs using shear exfoliated graphene as electrodes as well as active triboelectric layer deposited by a simple solution process. Graphene in combination with polymers such as polydimethylsiloxane (PDMS) were used to produce TENG devices using low-cost solution processing methods. Device electrical power generation was tested with a cyclic physical stimulus for better control and understanding of device output. The triboelectric response of these materials showed open circuit voltages (Voc) and short-circuit currents (Isc)of approximately 233 V and 731 nA respectively when stimulated at 1.5 Hz. A power density of 13.14 µW/cm2 under a load of 200 MΩ was achieved, which can be 40 times higher when compared to devices made with aluminum and PDMS. These results demonstrate the potential of solution process for low-cost triboelectric devices for self-sustainable wearable portable nanogenerators on health and security applications using contact and positional sensors.